(untitled) (Journal of the College of Basic Education, 2023)
Literary and linguistic studies have expanded in the last two decades of this century.Arab culture, where approaches crystallized closer to the linguistic field than other fields.The structural approach appeared with its strict procedural tools, and this approach developed to producethe formative structure, which refused but to restore life to man and society, andIt departs from the field of linguistics, such as stylistic and poetic..etc. However, these approaches, in spite ofConvergence or divergence in procedural tools and situations, she was unable to enter the world of theater completely.Especially the literary text in particular. It is true that these approaches have known successes of varying importance.in the fields of written creativity, especially in the field of poetry and the fictional story, but she stood at a lossIn the face of the danger of dramatic art, because this art does not stop at the limits of the written orHowever, this extends to tools that go beyond the pure linguistic approach. Therefore, it was necessary toFinding an approach that is able to possess these non-linguistic tools in the theatrical literary text.An approach that treats signs as languages having the same aesthetic or ideological value to a language.written or spoken.